Sosialisasi Konsep Pariwisata Berkelanjutan untuk Meningkatkan Kesadaran Masyarakat dan Konservasi Mangrove - Elyanta, Marciella; Dalimunthe, Femmy Indriany; Hutahaean, Theresia; Kamal, Mustafa; Ngatemin, Ngatemin (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Tanjung Rejo Tourism Village is the only mangrove tourism village in Deli Serdang Regency, North Sumatra. The priority problem that occurs at the service location is that the people do not yet understand that preserving mangroves can provide prosperity for the community. People still like to cut down mangroves to sell as charcoal or make full-fledged fish ponds. Community’s indifference in preserving mangrove forests can also be caused by their lack of involvement in mangrove forest management. The purpose of holding community service in the Tanjung Rejo is to open the insight of the people regarding the importance of managing mangrove forest resources and in turn will ensure the sustainability of these natural resources. The method is socialization in the form of lectures, discussions and making action plans. The results are community/partners were very enthusiastic about the socialization provided by the PKM Village Development Team. Through the outreach provided, community/partners can understand the concept of sustainable tourism and can develop action plans to implement the sustainable tourism agenda in the Tanjung Rejo Tourism Village. The conclusion and suggestion from the implementation of this PKM is the creation of an action plan to be implemented in Tanjung Rejo village.